Peran Pondok Pesantren Modern Baitussalam Dalam Menguatkan Nilai Aqidah Islam Masyarakat Desa Naga Jaya 1 Kec. Bandar Huluan - Novi Adriani; Maraimbang Maraimbang; Muhammad Hidayat (UIN Sumatera Utara, 2022)
This journal is the result of research with a policy research flow that aims to describe and understand the Role of Baitussalam Modern Boarding School in Strengthening the Value of Islamic Aqidah of Naga Jaya Village Community I Bandar Huluan Subdistrict, using qualitative research methods. The purpose of this study is to find out how the role of Pondok Pesantren Baitussalam in strengthening the value of Islamic Aqidah in Naga Jaya Village Community 1 district of Bandar Huluan. This type of research is field research conducted using observation methods and direct interviews to the target object, namely by conducting interviews to the caregivers of Baitussalam Modern Boarding School and community residents in Naga Jaya Village 1 Bandar Huluan District simalungun which is considered to have an important role in providing information to get sources and materials that are the object of research, that is to know the nature of Aqidah's development of the community around Pondok Pesantren Modern Baitussalam. The results showed that the role of Pondok Pesantren Modern Baitussalam, has a fairly good role in strengthening the value of Islamic Aqidah community of Naga Jaya village 1 district of Bandar Huluan. What is known from the caretaker of baitussalam boarding school since its establishment in 1864 until now teaches the value of aqidah, until now also the community has carried out the studies and celebrations of Islamic holidays. The caretaker of Baitussalam boarding school is also very intense in forming understandings or teachings that are considered khurafat in sharia or purification of Islam.